THE EFFECT OF AUDIT LAG, AUDITOR’S REPUTATION, COMPANY SIZE, AND COMPANY GROWTH ON GOING-CONCERN AUDIT OPINION - Ramadhani, Runaily; Anisma, Yuneita; Safitri, Devi (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
The purpose of this study is to test and demonstrate empirically the effects of audit lag, auditor’s reputation, company size, and company growth on going-concern audit opinion. This study is a quantitative study with secondary data sources. The population of this study includes 58 mining companies registered on the IDX in 2017-2021. The samples consist of 25 companies which were selected through a purposive sampling technique. The hypothesis was tested using logistic regression analysis with the IBM SPSS 25 application. According to the logistic regression test, audit lag and company size have a positive impact on going-concern audit opinion. However, neither auditor reputation nor company growth has any effect on going-concern audit opinion.